An improved prediction of the human in vivo intestinal permeability and BCS class of drugs using the in vitro permeability ratio obtained for rat intestine using an Ussing chamber system. (October 2013) - Li, Hong; Jin, Hyo-Eon; Shim, Won-Sik; Shim, Chang-Koo
Abstract : The Biopharmaceutics Classification System (BCS) was developed to facilitate estimation of the in vivo pharmacokinetic performance of drugs from human intestinal permeability and solubility. However, the measurement of human in vivo intestinal permeability, unlike that of solubility, is problematic and inefficient. Thus, rat in vitro intestinal permeability results obtained via the Ussing chamber technique are often used instead. However, these data could be unreliable due to difficulty in maintaining the viability of the dissected intestinal membrane in the Ussing chamber. Therefore, a more efficient method to obtain a reliable in vitro permeability is mandatory. Here, we propose a new approach by introducing a novel factor called the permeability ratio (PR). Basically, PR is a rat in vitro intestinal permeability obtained from the Ussing chamber, which is then corrected by the permeability of lucifer yellow, a paracellular permeability marker. To prove the validity of the method, 12 model drugs representing different BCS classes were tested, and the correlation with human in vivo intestinal permeability was high. More importantly, the new method perfectly classified all 12 model drugs. The results indicate that PR is a reliable factor with high correlation to human in vivo intestinal permeability, which can further be used to accurately predict the BCS classification.